Identification, molecular characterization, and biology of a novel quadrivirus infecting the phytopathogenic fungus Leptosphaeria biglobosa - Shah,UA; Kotta-Loizou,I; Fitt,BDL; Coutts,RHA (Viruses, 2019)
Here we report the molecular characterisation of a novel dsRNA virus isolated from the filamentous, plant pathogenic fungus Leptosphaeria biglobosa and known to cause significant alterations to fungal pigmentation and growth and to result in hypervirulence, as illustrated by comparisons between virus-infected and -cured isogenic fungal strains. The virus forms isometric particles approximately 40–45 nm in diameter and has a quadripartite dsRNA genome structure with size ranges of 4.9 to 4 kbp, each possessing a single ORF. Sequence analysis of the putative proteins encoded by dsRNAs 1–4, termed P1–P4, respectively, revealed modest similarities to the amino acid sequences of equivalent proteins predicted from the nucleotide sequences of known and suspected members of the family Quadriviridae and for that reason the virus was nominated Leptosphaeria biglobosa quadrivirus-1 (LbQV-1). Sequence and phylogenetic analysis using the P3 sequence, which encodes an RdRP, revealed that LbQV-1 was most closely related to known and suspected quadriviruses and monopartite totiviruses rather than other quadripartite mycoviruses including chrysoviruses and alternaviruses. Of the remaining encoded proteins, LbQV-1 P2 and P4 are structural proteins but the function of P1 is unknown. We propose that LbQV-1 is a novel member of the family Quadriviridae.